A novel role of proteasomal β1 subunit in tumorigenesis. Issue 4 (16th July 2013) - Yuan, Fuqiang; Ma, Yana; You, Pan; Lin, Wenbo; Lu, Haojie; Yu, Yinhua; Wang, Xiaomin; Jiang, Jie; Yang, Pengyuan; Ma, Qilin; Tao, Tao
Abstract : p27 Kip1 is a key cell-cycle regulator whose level is primarily regulated by the ubiquitin–proteasome degradation pathway. Its β1 subunit is one of seven β subunits that form the β-ring of the 20S proteasome, which is responsible for degradation of ubiquitinated proteins. We report here that the β1 subunit is up-regulated in oesophageal cancer tissues and some ovarian cancer cell lines. It promotes cell growth and migration, as well as colony formation. β1 binds and degrades p27 Kip1 directly. Interestingly, the lack of phosphorylation at Ser 158 of the β1 subunit promotes degradation of p27 Kip1 . We therefore propose that the β1 subunit plays a novel role in tumorigenesis by degrading p27 Kip1 .